Heartwood, sapwood and bark content of Bombacopsis quinata in Costa Rica - Pérez, D.; Kanninen, M.; Matamoros, F.; Fonseca, W.; Chaves, E. (2004)
The Costa Rican government has promoted the establishment of high yielding plantations, expecting to produce high quality timber. Nowdays the management of some species have been uncertain, since wood quality and yield are becoming lower than expected. Heartwood content is a determinant characteristic for Bombacopsis quinata, a widely appreciated species in the country. The aim of this study was to evaluate the heartwood, sapwood and bark content of young and advanced aged B. quinata trees. The research was based on the hypothesis that heartwood content increases with increasing age. By means of steam analysis, the heartwood, sapwood, and bark volume was measured on trees of different ages (10 to 27 years). The highest heartwood proportion found in B. quinata was 13,6%, and the lowest o.1%. The sapwood ranged between 70.0 and 87.2% while the bark, from 9.4 to 23% of the total stem volume. No clear differences in heartwood content could be observed between trees of similar age from dry and wet zones. Rotation period for B. quinata in Costa Rica should be extended to produce high quality timber with increased heartwood content.